The Routledge companion to literature and disability - Hall, Alice (Literature professor) (Abingdon, Oxon ; New York, NY : Routledge, 2020)
The Routledge Companion to Literature and Disability brings together some of the most influential and important contemporary perspectives in this growing field. The book traces the history of the field and locates literary disability studies in the wider context of activism and theory. It introduces debates about definitions of disability and explores intersectional approaches in which disability is understood in relation to gender, race, class, sexuality, nationality and ethnicity. Divided broadly into sections according to literary genre, this is an important resource for those interested in exploring and deepening their knowledge of the field of literature and disability studies.
OCLC-licensed vendor bibliographic record.
Keywords: Disabilities in literature; LITERARY COLLECTIONS / General; LITERARY CRITICISM / General